Rancang Bangung Sistem Informasi E-Learning Berbasis Web di SMK Karya Permata Rancaekek - Murti, Arti Arsiati; Suyatna, Nano (Ma'soem University, 2024)
The research conducted on the learning process of new students revealed numerous identified issues. These issues include suboptimal learning outcomes resulting from time constraints and inadequate learning materials due to limited access to information provided by teachers.The research conducted on the learning process of new students revealed numerous identified issues. These issues include suboptimal learning outcomes resulting from time constraints and inadequate learning materials due to limited access to information provided by teachers.The website has been developed utilizing the PHP (Hypertext Preprocessor) web programming language and incorporates a MySQL database. The primary objective of this system's design is to enhance student learning by enabling access to educational resources through an internet network. This accessibility feature is anticipated to streamline the process of obtaining information and materials, ultimately leading to an enhanced learning experience.